Evaluating ChatGPT's Role in Assessing Turkey's Medical Tourism Trends - Akpur, Akın; Enes, Kemal (Jordan Medical Journal, 2024)
Background and Aims: The primary objective of this study is to evaluate the performance of the ChatGPT as an expert in the field of medical tourism. Another objective of this study is to assess its evaluations regarding the current state and future prospects of medical tourism in Turkey from an artificial intelligence perspective. Methods: Within the scope of the study's objectives, questions were created for ChatGPT regarding the current state and future prospects of medical tourism in Turkey. First, the draft questions were prepared by the authors of this article using the literature. All questions were evaluated by experts through online interviews. Totally 8 experts have been evaluated the questionnaires. These experts consisted of two tourism professors who had research on medical tourism, three major medical tourism hospital managers, one reconstructive aesthetician clinic owner, and the Turkish Healthcare Travel Council Founding Chairman. The second step of the research questionnaire was applied to the ChatGPT Model 4, which was trained as a medical tourism expert. than test the answers of the AI used the tools “Completeness of content, Lack of false information in the content, Evidence supporting the content, Appropriateness of the content, and Relevance,” referred as CLEAR. All answers were evaluated by 41 experts who had articles and research on medical tourism in Turkey. To explain the methodology appropriately, reporting was conducted using the METRICS checklist, which was prepared for artificial intelligence studies. Results: TThe general answers of ChatGPT 4-o were accurate, informative, and helpful, providing a good overview of medical tourism in Turkey. However, the responses lacked detail, did not provide evidence-based information, and did not always address the nuances and cultural/social impacts of medical tourism. ChatGPT 4-o views the future of Turkey’s medical tourism as shiny and will force the lead in general. Conclusions: This study is important for revealing data on the current and future state of medical tourism through artificial intelligence. However, only a few studies have been conducted on artificial intelligence and medical tourism. To the best of our knowledge, there is no existing literature that systematically evaluates the ChatGPT responses of medical tourism experts. In this regard, it is believed that the study will benefit both academics and practitioners.